(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Sympatric lizard species co-occurring in the same habitat patch provide tractable natural systems for investigating the relative contributions of pre-zygotic and post-zygotic reproductive isolation mechanisms to species coexistence, because incomplete isolation at any stage generates observable hybridisation whose genetic and phenotypic consequences are detectable with contemporary molecular and morphometric tools. This study quantified reproductive isolation mechanisms in three sympatric lizard species pairs in the central Mediterranean — Podarcis muralis / P. siculus (Lacertidae), Lacerta bilineata / L. agilis (Lacertidae), and Algyroides nigropunctatus / Dalmatolacerta oxycephala (Lacertidae) — at 24 sympatric localities across Switzerland, Italy, and Croatia. Four reproductive isolation mechanisms were quantified: (i) microhabitat segregation (thermal preference overlap: Dhat4; habitat use separation); (ii) temporal isolation (activity period overlap: Dhat4 from continuous temperature-datalogger body temperature tracking); (iii) male-male competition outcomes (staged encounters; n = 284); and (iv) premating isolation via female mate choice (two-choice trials; n = 186 females). Genetic admixture was quantified from 14,842 RADseq SNPs in 486 individuals. Total reproductive isolation index (RI(total)) ranged from 0.42 (P. muralis / P. siculus; weakly isolated) to 0.84 (A. nigropunctatus / D. oxycephala; strongly isolated). Pre-mating mechanisms contributed 68.4 ± 8.4% of total isolation, with microhabitat segregation (mean isolation contribution 0.32 ± 0.08) and female mate choice (0.28 ± 0.06) being the dominant barriers. ADMIXTURE detected F1 and F2 hybrids at 6 of 24 sympatric localities in the P. muralis / P. siculus pair, consistent with incomplete but functional pre-mating isolation. RADseq FST outlier analysis identified colour pattern and pheromone receptor loci as the primary genomic targets of divergent selection maintaining species boundaries. These results confirm that sympatric lizard coexistence is maintained primarily by microhabitat segregation and female discrimination, with post-mating barriers playing a secondary but detectable role in the most divergent pairs.